Knowledge, Attitude, and Practice in Management of Childhood Fever Among Saudi Parents - Shalam Mohamed Hussain PhD; Osama Al-Wutayd MD, SBCM; Ahmed Hamad Aldosary MD; Abdullah Al-Nafeesah MD; Ashwaq AlE'ed MD; Modhi Saleh Alyahya MD; Anfal Saleh Alfeneekh MD; Sirin Ahmed AlKadi Intern; Ghaida Abdulrahman Alghasham Intern; Ghadah Abdulaziz Aloyaidi Intern (SAGE Publishing, 2020)
Fever is considered as a frequent symptom in childhood and is the cause of almost 65% to 70% of pediatric visits. Saudi Arabia has about 10% of child population (under 4 years of age), imposing a high burden of childhood illnesses including fever. A total of 1700 questionnaires were distributed to Saudi parents with children visiting pediatric clinic. Most of the participants were mothers (77.4%). A temperature of 38.0 °C was defined fever by 42% of participants. The majority of parents (80%) believed seizure is the consequence of untreated high fever. A total of 72.5% indicated that 40.7 to 43.20°C is the highest temperature that can be reached if untreated. There was a statistically significant relationship between mothers and fathers for overall knowledge, attitude, and practice scores. This study indicates that numerous misconceptions still persist regarding fever as more than 90% of parents demonstrated undue fear of consequent body damage from fever and also believed antibiotics can reduce high temperature.